Law or finance: evidence from Finland - Ari Hyytinen; Iikka Kuosa; Tuomas Takalo (Bank of Finland, 2002)
Although it is widely acknowledged that the benefits of corporate governance reform could be substantial, systematic evidence on such reforms is scant.We both document and evaluate a contemporary corporate governance reform by constructing 18 measures of shareholder and creditor protection for Finland for the period 1980-2000.The measures reveal that shareholder protection has been strengthened whereas creditor protection has been weakened.We also demonstrate how the reform is consistent with a reorganisation of the Finnish financial market in which a bank-centred financial system shifted from relationship-based debt finance towards increasing dominance by the stock market.We find evidence that the development of shareholder protection has been a driver of the reorganisation, whereas the changes in creditor protection have mirrored market developments.
URN:NBN:fi:bof-20140807417
Keywords: E50; G24; G32; 330; corporate finance; financial intermediation; corporate governance